2014
DOI: 10.1016/j.molmet.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of IRS-1 in adipose tissue of offspring of obese mice is programmed cell-autonomously through post-transcriptional mechanisms

Abstract: We determined the effects of maternal diet-induced obesity on offspring adipose tissue insulin signalling and miRNA expression in the aetiology of insulin resistance in later life. Although body composition and glucose tolerance of 8-week-old male offspring of obese dams were not dysregulated, serum insulin was significantly (p<0.05) elevated. Key insulin signalling proteins in adipose tissue were down-regulated, including the insulin receptor, catalytic (p110β) and regulatory (p85α) subunits of PI3K as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
112
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(123 citation statements)
references
References 46 publications
(42 reference statements)
10
112
0
1
Order By: Relevance
“…This targeting association has also been reported in colon cancer cells and adipocytes (22,23). Furthermore, it has been demonstrated that insulin-like growth factor-I receptor signaling contributes to the development of endometrial hyperplasia, the precursor to EC (24), and that IRS1 is a key mediator in oncogenic insulin-like growth factor signaling (25).…”
Section: Discussionsupporting
confidence: 68%
“…This targeting association has also been reported in colon cancer cells and adipocytes (22,23). Furthermore, it has been demonstrated that insulin-like growth factor-I receptor signaling contributes to the development of endometrial hyperplasia, the precursor to EC (24), and that IRS1 is a key mediator in oncogenic insulin-like growth factor signaling (25).…”
Section: Discussionsupporting
confidence: 68%
“…Large fold changes were also observed at miRNAs known to be involved in metabolism. miR-126, a negative regulator of insulin signaling previously shown to be responsive to diet-induced maternal obesity in offspring adipose tissue was upregulated by 2.5-fold: 22 our data implies that diet also impacts directly on miR-126 expression in the heart.…”
Section: Discussionsupporting
confidence: 59%
“…The model of maternal diet-induced obesity used here has been described previously (20). Briefly, female C57BL/6J mice were fed ad libitum a standard control chow diet (2.56 kcal/g; fat, 7.42% [kcal]; RM1, Special Diet Services) or a highly palatable energy-rich obesogenic diet (6.79 kcal/g; fat, 45% [kcal]; 45% AFE Fat, Special Diet Services) and sweetened condensed milk (55% simple sugar, 8% fat, 8% protein [wt/wt]; Nestle, fortified with mineral and vitamin mix AIN93G) from 4 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular analyses that have adopted a candidate approach have demonstrated that diet-induced obesity during pregnancy can lead to programmed effects on mRNA, micro RNA (miRNA), and protein expression in adipose tissue. These include studies that have shown significant reduction in expression of glucose transporter type 4 in adipose tissue, which can selectively cause insulin resistance (19), and our own studies, which demonstrate up-regulation of miR-126 that can directly influence insulin receptor substrate-1 protein expression (20). …”
mentioning
confidence: 99%